The replacement of the International Accounting Standard 39 (Financial Instruments: Recognition & Measurement) by the International Financial Reporting Standard 9: The possible impacts on the Cyprus Banking Sector and how this might reflect on the banks’ balance sheets (using sensitivity analysis on the annual report of “Bank of Cyprus Group”) - Georgiou, Tryfonas (Department of Commerce, Finance and Shipping, Faculty of Management and Economics, Cyprus University of Technology, 2018)
In the current thesis, it will be evaluated how the replacement of accounting standard on measurement and recognition of financial instruments (IAS 39 to IFRS 9) will affect the global banking sector, with a closer look to the Cyprus Banking Sector. The guidelines of the old IAS 39 and new IFRS 9 accounting standard will be explained in detail. The variety of the financial instrument in banks’ Balance Sheet will be mentioned considering the Annual Reports of the biggest European Banks. There will be a reference to the historical events that led to the replacement of IAS 39. In the last sections, a closer look to the Cyprus banking sector will be made by referencing the estimated impact of the new measurement and recognition of financial instruments on the Cyprus banks’ Balance Sheets. A sensitivity analysis will be developed on the Balance Sheet of Bank of Cyprus by taking into consideration the new guidelines of IFRS 9. Further, discussion and conclusion based on the findings follows.
Keywords: Accounting standard; Financial instruments (IAS 39 to IFRS 9); Global banking sector